South Florida Conceptual Model - H. Carl Fitz (EDIS)
SL320, a 7-page illustrated fact sheet by H. Carl Fitz, describes this model that explores the fundamental linkages among the Everglades landscape and the human dimension of the South Florida region — societal valuation, urban and agricultural development, water management, and everglades dynamics. Includes sources for further reading. Published by the UF Department of Soil and Water Science, June 2010.